The Impact of a Brain Exercise Program on Cognitive Functions Among Rural Thai Older Adults: A Quasi-Experimental Study - Leethong-in, Mayuree; Piyawattanapong, Sirimart; Sommongkol, Sawitree; Thiengtham , Supavadee; Subindee, Suttinan; Komniyom, Nutda; Chotchaisthit, Patchara; Chuen-arom, Chanokruethai (Asia-Pacific Journal of Science and Technology, 2021)
Brain exercise is important to maintain and improve cognitive functions in older adults. Most of the brain training programs, however, was developed for highly educated groups in urban areas so they have limitations when applied to people who live in rural areas where studies showed a high rate of cognitive decline. The need to develop an effective brain-training program for rural people groups is indicated. This quasi-experiment study aims to examine the effects of cognitively stimulating program on cognitive functions. Fifty older adults in Northeastern Thailand were divided into a control group and intervention group equally. The study instruments were general information sheet, Montreal Cognitive Assessment (MoCA) Thai version with interrater reliability of 0.86, and the Brain Exercise program with content validity of 0.90. The average age of the participants in the intervention group was 68.08 years (S.D. = 5.70) and the control group was 69.14 years (S.D. = 5.64). The study results showed that post-intervention cognitive scores of the intervention group were significantly higher than baseline (p=.000**). Also, the post-intervention cognitive scores of older adults in the intervention group were significantly higher than those who were in the control group (p=.042*). The results indicated that the Brain Exercise program could be applied to improve cognition, especially in healthy young-old age groups.